2017
DOI: 10.1002/smll.201700629
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Gold Nanocone Array Surfaces as a Tool for Regulating Neuronal Behavior

Abstract: Accelerated neurite outgrowth of rat cortical neurons on a flexible and inexpensive substrate functionalized with gold nanocone arrays is reported. The gold nanocone arrays are fabricated on Teflon films by a bottom-up approach based on colloidal lithography followed by deposition of a thin gold layer. The geometry of nanocone arrays including height and pitch is controlled by the overall etching time and template polystyrene beads size. Fluorescence microscopy studies reveal high viability and significant mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
(68 reference statements)
2
19
1
Order By: Relevance
“…Nanosphere lithography (also referred to as colloidal lithography) uses the self‐assembly of polymer or microgel‐based nanospheres on a surface . A wide range of variants exist, for a more in depth discussion see the review of Wang et al Controlling the type and size of particle deposited, the surface chemistry, and deposition conditions allows either well‐defined high‐density packing or lower‐density stochastic patterns …”
Section: Fabrication Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosphere lithography (also referred to as colloidal lithography) uses the self‐assembly of polymer or microgel‐based nanospheres on a surface . A wide range of variants exist, for a more in depth discussion see the review of Wang et al Controlling the type and size of particle deposited, the surface chemistry, and deposition conditions allows either well‐defined high‐density packing or lower‐density stochastic patterns …”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…Nanosphere lithography (also referred to as colloidal lithography) uses the self-assembly of polymer or microgel-based nanospheres on a surface. [167,[179][180][181] A wide range of variants exist, for a more in depth discussion see the review of Wang et al [155] Controlling the type and size of particle deposited, the surface chemistry, and deposition conditions allows either well-defined high-density packing [27] or lower-density stochastic patterns. [122] Plasma etching and gel-swelling techniques can also be used to vary the pitch and diameter of the pattern, [153,182] which can then be transferred to the surface via multiple methods, such as ion bombardment [183] or metal-assisted chemical etching.…”
Section: Nanosphere and Colloidal Lithographymentioning
confidence: 99%
“…Brüggemann et al showed staining of neuronal actin filaments with almost no growth cones for gold nanopillar arrays, while a broad growth cone was formed on planar substrates . A direct aspect of the growth cone appearance was reported by Toma et al Accelerated neurite outgrowth of neurons was induced by functionalized gold nanocone arrays …”
Section: Resultsmentioning
confidence: 85%
“…58 A direct aspect of the growth cone appearance was reported by Toma et al Accelerated neurite outgrowth of neurons was induced by functionalized gold nanocone arrays. 59 To subsume all results presented so far, we can note that the PPX material shows a harmful chemical effect on the cell viability and neurite formation, which becomes apparent if control and PPX samples are compared. The adhesion impairing properties of the PPX is presumably related to their hydrophobic nature according to the high contact angle of the material.…”
Section: Substrate Topographymentioning
confidence: 97%
“…However, having the cells in a matrix complicates post processing and analysis. By culturing in 2.5D on substrates with an alternative topology like for example membranes [7][8][9][10], nanostructures [11,12], or even pillars [13][14][15][16], some of the benefits of 3D culturing can be obtained while providing the possibility of conventional post-culture This work was performed in the laboratories of Winnie E. Svendsen and of Helle S. Waagepetersen handling. Both ordered and random structures have been demonstrated to affect cell growth.…”
Section: Introductionmentioning
confidence: 99%